2019
DOI: 10.1017/jfm.2019.165
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic flow around a cylinder with a permeable high-porosity insert: experiment and numerical simulation

Abstract: Results of experimental and numerical investigations of a supersonic flow around a cylinder with a frontal gas-permeable insert made of a high-porosity cellular material are presented. The measurements are performed in a T-327 supersonic blowdown wind tunnel at the free-stream Mach numbers $M_{\infty }=4.85$, 7 and 21 in the range of the unit Reynolds numbers $Re_{1\infty }=(0.6{-}13.5)\times 10^{6}~\text{m}^{-1}$. The drag coefficients for a cylinder with an aerospike and a cylinder with a frontal gas-permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…2005; Maslov et al. 2005). Wang & Zhong (2011) indicated that a porous surface can modify the phase difference between the pressure and the normal velocity near the wall; thus, a porous surface is considered below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2005; Maslov et al. 2005). Wang & Zhong (2011) indicated that a porous surface can modify the phase difference between the pressure and the normal velocity near the wall; thus, a porous surface is considered below.…”
Section: Resultsmentioning
confidence: 99%
“…This initial work is currently limited to the linear growth stage of the second mode, where LST still applies. Porous materials have been widely used in the study of hypersonic boundary layers (Fedorov et al 2001;Chokani et al 2005;Maslov et al 2005). Wang & Zhong (2011) indicated that a porous surface can modify the phase difference between the pressure and the normal velocity near the wall; thus, a porous surface is considered below.…”
Section: Porous-surface Modelmentioning
confidence: 99%